Focused in vivo Delivery of Plasmid DNA to the Porcine Vascular Wall via Intravascular Ultrasound Destruction of Microbubbles - Phillips, Linsey C. (S. Karger AG, 2010)
BACKGROUND: Safety concerns associated with drug-eluting stents have spurred interest in alternative vessel therapeutics following angioplasty. Microbubble contrast agents have been shown to increase gene transfection in vivo in the presence of ultrasound. Objectives/Methods: The purpose of this study was to determine whether an intravascular ultrasound (IVUS) catheter could mediate plasmid DNA transfection from microbubble carriers to the porcine coronary artery wall following balloon angioplasty. RESULTS: In the presence of plasmid-coupled microbubbles in vitro only cells exposed to ultrasound from the modified IVUS catheter significantly expressed the transgene. A porcine left anterior descending coronary artery underwent balloon angioplasty followed by injection and insonation of microbubbles from the IVUS catheter at the site of angioplasty. After 3 days, an approximately 6.5-fold increase in transgene expression was observed in arteries that received microbubbles and IVUS compared to those that received microbubbles with no IVUS. CONCLUSIONS: The results of this study demonstrate for the first time that IVUS is required to enhance gene transfection from microbubble carriers to the vessel wall in vivo. This technology may be applied to both drug and gene therapy to reduce vessel restenosis.